Green Synthesis and Comprehensive Characterization of Selenium Nanoparticles: Towards Sustainable Biomedical and Environmental Applications - Preethi, P.; Annammal, A. Antony; Geetha, B. (Asian Journal of Biological and Life Sciences, 2025)
Background and Rationale: Nanotechnology has revolutionized various scientific disciplines, with Selenium Nanoparticles (SeNPs) demonstrating exceptional potential due to their unique physicochemical properties and applications in medicine, agriculture, and environmental sciences. However, conventional synthesis methods often employ toxic chemicals, posing significant environmental and health risks. Green synthesis of nanoparticles using plant extracts offers a sustainable and eco-friendly alternative. This study focuses on the green synthesis of SeNPs utilizing the aqueous leaf extract of Anacardium occidentale, optimizing the synthesis conditions, and characterizing the resulting nanoparticles. Materials and Methods: The green synthesis of SeNPs was conducted using aqueous leaf extract of Anacardium occidentale as a reducing and stabilizing agent. The synthesis process was optimized using the orthogonal test of the Taguchi design experiment. Characterization techniques, including UV-vis spectroscopy, Fourier-Transform Infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Zeta potential analysis was done to confirm the synthesis and stability of the Selenium Nanoparticles. Results and Discussion: The optimal conditions for the green synthesis of Selenium Nanoparticles were a reaction time of 1 hr, citric acid concentration of 0.04 M, aqueous leaf extract concentration of 1.0 mg/mL, and pH 7.5, yielding nanoparticles with an average particle size of 121.9 nm. The UV-vis spectroscopy results highlighted the surface plasmon resonance at 270 nm, indicative of small nanoparticle size. FTIR analysis confirmed the involvement of specific functional groups from the leaf extract in the reduction and stabilization processes. SEM and TEM analyses corroborated the spherical shape and uniform size distribution of the Selenium Nanoparticles. The zeta potential value of -23.5 mV indicated good colloidal stability. These findings demonstrate the effectiveness of Anacardium occidentale leaf extract in producing stable, spherical SeNPs via an eco-friendly approach. Conclusion: Green synthesis of SeNPs from Anacardium occidentale leaf extract minimizes adverse environmental and health impacts associated with conventional methods.
Keywords: Characterisation study; Condition optimisation; Green synthesis; Selenium nanoparticles